The Service Quality of Education in Primary School IAS Al-Jannah - Muhammad Suherlan Amel Herlan; Matin Matin; Siti Rochanah (Program Studi Manajemen Pendidikan, 2020)
ABSTRACT The objective of this research is to describe the service quality by focusing to the responsiveness of service; the competency of service; and the usage of school facilities. This is qualitative research with a case study method conducted in Primary School IAS Al-Jannah, Depok, in 2019. The data was collected by conducting interviews, observation, recording, and collecting documents. The reliability of this research is confirmed by triangulation method which included sources of data, method of finding the data, and the theories. Results of this research showed that (1) teachers can actualize themselves through activities that support school programs which make them experience more self-determination, meaning, competence, and impact regarding their role in the working environment; (2) factors that caused costumer’s loyalty to the educational services in Primary School IAS Al-Jannah are the supportive environtment; positive changes on their children’s not only academically but also their behavior by implementing better daily religious practice; their children can speak English fluently; and have discipline time management. (3) Primary School IAS Al-Jannah has adequate facilities and infrastructures which support the learning process.